Modelando a percepção: o ambiente do patrimônio cultural edificado na regulação da forma urbana - Sousa, Carlos Eugênio Moreira de (2018)
he preservation of the relationships that a built cultural heritage maintains with its surroundings is a fundamental issue in the study of the urban dimension of heritage. However, their conflicting interaction with urban “development” policies, plans and projects has been a recurring problem. This research investigates this issue and tries to offer possible coping strategies. To do so, it traces the origins of these issues from the point of view of heritage preservation, where the notion of environment (and the related terms it aggregates, such as ambience, surroundings, neighborhood, visibility, etc.) is investigated from three approaches: historical (seeking the origins of the term), ontological (searching for meanings of basic terms), and practice (bringing examples of how the question has been treated in concrete cases). It can be seen that the “invention” of urban heritage (of which the notion of environment is a fundamental part) has intimate relations with the origin of urbanism as discipline and that the historical path that separated the two subjects only intensified the conflicts between both. Thus, in an attempt to construct a further approchement between these knowledge domains, an overview of the posture of urbanism in front of the contemporary city is set up, where the use of information models (codifying the stages of problem formulation, generation of alternatives and evaluation of results in a heuristic and incremental process) emerges as an interesting paradigm to be pursued. It is suggested, therefore, that the (r)approximation of the disciplines can be done through a two steps strategy: (1) the creation of an informational framework in computational environment as a representation device of the city, following the structure of a City Information Model (CIM); (2) the creation of a tool set for the evaluation of environmental relations of built cultural heritage that operates within the aforementioned framework. In this way, it becomes possible to model an analysis process that provides useful information for the demarcation and management of surrounding areas of historical buildings, supporting the negotiations between the various stakeholders. As a result, a functional prototype is presented, capable of retrieving georeferenced data stored in a remote database, built by the laboratory to which the research is linked in the university. Finally, use tests are presented in the confrontation of concrete cases, using data from the city of Fortaleza - CE, collected with the municipal administration and cultural heritage agencies. As a prototype, the conclusions are focused on making a critical review of the process, outlining the difficulties and limitations, as well as pointing out the potentialities and paths for further developments.